2010
DOI: 10.5964/ejop.v6i4.228
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the psychological impact of a Mindfulness-Based Stress Reduction Program on highly sensitive persons

Abstract: Background. The mindfulness Based Stress Reduction (MBSR) program has been provided in a variety of settings, and for a variety of individuals. Over two decades of research show that its effectiveness has been made plausible. However, the effects of MBSR interventions on highly sensitive persons (HSPs) have not been examined to date.Aim. This study investigated the effects of participation in a MBSR program on symptoms of stress, social anxiety, self-acceptance, emotional empathy, personal growth, and selftran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The growth of PGIis conducive to improving the positive attitude of self-improvement, which makes the SWB index relatively higher. This is similar to previous ndings that mindfulness training can help develop PGI(Soons et al, 2010;Loo et al, 2014). Studies have shown that mindfulness is positively correlated with PGI (Yimeng, 2020).…”
supporting
confidence: 91%
“…The growth of PGIis conducive to improving the positive attitude of self-improvement, which makes the SWB index relatively higher. This is similar to previous ndings that mindfulness training can help develop PGI(Soons et al, 2010;Loo et al, 2014). Studies have shown that mindfulness is positively correlated with PGI (Yimeng, 2020).…”
supporting
confidence: 91%
“…Mindfulness means developing a non-judgmental awareness of an object. Mindfulness based interventions are potential mental health instruments (Soons et al, 2010). More mindful individuals report less negative mood after the conflict occurs (Burke, 2009).…”
Section: Multivariate Testsmentioning
confidence: 99%
“…Mindfulness based intervention is a potential equipment of mental health promotion (Nyklíček et al, 2012;Soons et al, 2010). Mindfulness based intervention can enhance personal growth, selfacceptance, empathy, and self-transcendence as well as reducing the levels of stress and social anxiety (Soons et al, 2010). Being aware of the present moment and realizing that it is the only real time owned can be very beneficial for the mind and body (Widdett, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention had positive effects on participants with psychological problems and even severe psychiatric conditions. For instance, the mindfulness-based stress reduction program increased the highly sensitive participants’ scores of self-acceptance, mindfulness, and emotional empathy ( Soons et al, 2010 ). On completion of a positive psychology group therapy, participants with severe psychiatric conditions reported a significant improvement in self-acceptance and significant decreases in interpersonal sensitivity and depression ( Valiente et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%